A Robust Algorithm for Estimating Total Suspended Solids (TSS) Using Sentinel-2: Case Study in Coastal Waters of Teluk Awur, Jepara, Indonesia - Sabila, Anis Yasmin; Maslukah, Lilik; Wirasatriya, Anindya; Indrayanti, Elis; Prasetyawan, Indra Budi; Widada, Sugeng (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Total suspended solids (TSS) is an important parameter of water quality, so regular monitoring is necessary to prevent further marine pollution due to TSS. Remote sensing is one of the most effective and efficient methods to monitor TSS with cost-effective operations. The Sentinel-2 satellite is freely available to users with high spectral and spatial resolution (10m, 20m, 60m). Dynamic changes in coastal waters and their characteristics cause TSS retrieval algorithms built from available imagery having less optimal results in other water regions. This research aims to develop an empirical TSS algorithm model that specifically applies to the coastal waters of Teluk Awur, Jepara. The algorithm was developed using an empirical method through correlation between spectral values of Sentinel-2 imagery and in situ TSS values. Water sampling was conducted at 110 stations with a depth of 0.5 m on 22 July 2023 simultaneously collocated with Sentinel-2 image recording. Half of the data was used for algorithm tuning and the other half used for validation. The best regression analysis is found in the red band (B4) and the model is linear. The relatively good performance is shown by the coefficient of determination (R²) of 0.45, RMSE (3.40 mg.L-1), and MAPE (10.76%). The resulting algorithmic model was TSS (mg.L-1) =817.213*(B4)-0.959. This study shows that Sentinel-2 MSI images for TSS retrieval in the coastal waters of Teluk Awur could be applicable and the red band (B4) can be used for mapping TSS concentrations in the surrounding study area.